2018
DOI: 10.1111/vde.12524
|View full text |Cite
|
Sign up to set email alerts
|

A field trial in Thailand of the efficacy of oral fluralaner for the treatment of dogs with generalized demodicosis

Abstract: Fluralaner given at the label dose for flea and tick prevention is effective for the treatment of canine generalized demodicosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 9 publications
5
17
0
Order By: Relevance
“…In another uncontrolled eld study involving dogs with generalized demodicosis, in Thailand, a parasitological cure was observed in 100% of dogs (n = 67) within 3 months following treatment with orally administered uralaner [16]. This is consistent with our nding of a day 84 parasitological cure in 100% of dogs treated orally with uralaner and 96.1% of those receiving uralaner spot-on.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In another uncontrolled eld study involving dogs with generalized demodicosis, in Thailand, a parasitological cure was observed in 100% of dogs (n = 67) within 3 months following treatment with orally administered uralaner [16]. This is consistent with our nding of a day 84 parasitological cure in 100% of dogs treated orally with uralaner and 96.1% of those receiving uralaner spot-on.…”
Section: Discussionsupporting
confidence: 84%
“…mites, based on deep skin scrapings, and resolution of clinical signs. A non-blinded, uncontrolled, open-label study with orally administered uralaner provided evidence that those laboratory results could translate into eld e cacy [10,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Results from this controlled field study confirm results from a recent uncontrolled field study in which parasitological cures were observed over three months after fluralaner treatment in all dogs presented with juvenile-onset demodicosis [19]. Fluralaner treatment was also effective in dogs with adult onset demodicosis one month following a second treatment, administered 12 weeks after the first.…”
Section: Discussionsupporting
confidence: 83%
“…The efficacy of the treatment of demodicosis with isoxazolines has been described (Six et al, 2016;Snyder et al, 2017;Lebon et al, 2018). The oral treatment of this disease with fluralaner was effective as observed by other authors (Fourie et al, 2015;Bezerra et al, 2017;Duangkaew et al, 2018) with a single-dose administration. All the dogs obtained negative deep skin scrapings.…”
Section: Discussionmentioning
confidence: 63%
“…This compound was successfully used in parasitic skin diseases as miticidal therapy for sarcoptic mange (Romero et al, 2016) and demodicosis (Fourie et al, 2015;Duangkaew et al, 2018). Against generalized demodicosis, its administration resulted in 99.8% reduction of the mean mite observed by skin scrapings 28 days after treatment, while a 100% reduction was observed in 56 days after treatment (Fourie et al, 2015).…”
Section: Introductionmentioning
confidence: 99%